A Study of Student’s Misconception on Light Material and How to Reduce it Using LKS-Assisted PBL at Islamic Junior High School (SMP IT) Bina Amal Semarang (Physics Communication, 2018)
The existence of misconceptions could affect students’ problem solving ability in physics subject. The source of misconceptions could be derived from the text books that used by the students, from the students itself, as well as from the teachers. One of the learning models that might reduce the misconceptions on the topic of light was worksheets-assisted by problem based learning model. The purpose of this study was to identify the misconceptions experienced by the students of SMP IT BinaAmal on the topic of light, to analize misconceptions on the topic of light, to identify the descriptions of the students’ improvement on the concept of light, and to identify the worksheets-assisted problem based learning could develop the students’ scientific attitudes. The research method used mixed methods research using sequential explanatory design with pre-test and post-test Control Group Design. The sample of this research was the IX grade students of Hafshoh bint Abu Bakar class, and the IX grade students of Zaenab bint Jahsyi at SMP IT BinaAmal Semarang. The instruments that used in this study were questions and observation sheets. Based on the calculation of problem-solving test, in the experimental class obtained a gain factor of 0.553 with medium criteria, while the control class produces a gain factor of 0.249 with low criteria. The initial t-test shows thitung (-1.55) t table (1.68) that the experimental class is no better than the control class. The final t test shows thitung (2,481) t table (1.68) that the experimental class is better than the control class after the LKS-assisted PBL learning model is used. A very strong relationship between conceptual mastery and the reduction of misconceptions. LKS-assisted PBL learning influenced the results of the decrease in student misconceptions from 55.1% to 19.5% in the experimental class and a decrease in misconception from 59.4% to 31.9% in the control class. Based on the results of cognitive tests, obtained a qualitative data analysis, misconception that occurred in SMP IT Bina Amal on the concept of light, among others: regular reflections and diffuse; shadow formation, shadow space and shadow properties, light propagation; light sources and human processes can see things; and the law of refraction. Based on the result of the research, it is found that the LKS-based problem-based learning model is effective to reduce light misconception.